Construction Knitting - Gabriel, Nikki (Auckland University of Technology, 2015)
Construction as a term refers to the building of structural elements in a composition. This practice led methodology devises and investigates a design process that organises the arrangements of these structural elements as geometric shapes and parts for knitting. The design and production of these assemblages are led by principles of the geometric where hand making provides an essential foundation from which to generate innovative approaches for machine and digital knitting processes. The pattern grids of the geometric designs reveal more than just aesthetics, and are analysed as visual apparatus and conceptual tools that decode and simplify the technical complexities and superfluous jargon of knitting. This study considers how such narrative can be integrated into a more generic design dialogue, by referencing the geometric as the basic, primary and universal components of all design
Keywords: Hand Knitting; Three dimensional knitting; Domestic machine knitting; Geometric; Design process; Shima seiki